2019
DOI: 10.1177/1756829319833686
|View full text |Cite
|
Sign up to set email alerts
|

Computational study on the aerodynamics of a long-shrouded contra-rotating rotor in hover

Abstract: This paper aims to investigate the aerodynamics including the global performance and flow characteristics of a longshrouded contra-rotating rotor by developing a full 3D RANS computation. Through validations by current experiments on the same shrouded contra-rotating rotor, the computation using sliding mesh method and the computational zone with an extended nozzle downstream flow field effectively works; the time-averaged solution of the unsteady computation reveals that more uniform flow presents after the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…All the experiments aimed to explore the global characteristics of the shrouded system compared with free rotors and finally to provide the design criteria to guide the design of the SDR. According to the 2D numerical simulation results and preliminary experimental explorations made by the author, 22 the shroud which has inlet K i equal to 1.7 and outlet K e equal to 1.23 was chosen. All the experiments were made in hover status.…”
Section: Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…All the experiments aimed to explore the global characteristics of the shrouded system compared with free rotors and finally to provide the design criteria to guide the design of the SDR. According to the 2D numerical simulation results and preliminary experimental explorations made by the author, 22 the shroud which has inlet K i equal to 1.7 and outlet K e equal to 1.23 was chosen. All the experiments were made in hover status.…”
Section: Test Proceduresmentioning
confidence: 99%
“…Here, IRD 40 mm is the best performed locations for free rotors according to the previous studies. [22][23][24] It was hence chosen for comparison with shrouded system which has the best IRD 20.…”
Section: Comparison Of Shrouded and Open Double Rotor Systemsmentioning
confidence: 99%
“…Some studies showed that adaptively changing the load distribution by adjusting the impeller velocity of the rotor may effectively and optimally enhance the overall performance for all flow conditions. (29)(30)(31) Most of the previous studies on enhancing the performance of an MCRF system focused on passively adjusting suitable parameters to fit specific surging or designed working conditions. These methods have various limitations and fail under other undesigned working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The contra-rotating rotor system of 188 mm diameter with a relatively long shroud of the length of 1.17 rotor diameter was investigated by Huo et al 8 The static pressure distribution on the inner surface of the duct was measured and found to be lower in front of the upstream rotor in comparison with the open rotor. A suction peak on the leading edge of the duct contributes in a significant way into the increase in thrust of the ducted system.…”
Section: Introductionmentioning
confidence: 99%
“…Using ducted propellers in multicopter design implies a minimum shroud length for a given propeller diameter. Majority of studies of effects of shroud design parameters on the propulsive effectiveness were conducted for relatively long ducts (0.8-1.4 the propeller diameter [1][2][3][4][5]8 ). Both single propeller and two coaxial propeller systems were investigated, whereas studies on contra-rotating systems with very short ducts (of 0.17 the propeller diameter 6,7 ) showed only minor improvements in the propulsion performance.…”
Section: Introductionmentioning
confidence: 99%